2021
DOI: 10.1038/s41591-021-01527-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of SARS-CoV-2 variant mRNA vaccine boosters in healthy adults: an interim analysis

Abstract: The emergence of SARS-CoV-2 variants of concern (VOCs) and variants of interest (VOIs) with decreased susceptibility to neutralization has generated interest in assessments of booster doses and variant-specific vaccines. Clinical trial participants who received a two-dose primary series of the COVID-19 vaccine mRNA-1273 approximately 6 months earlier entered an open-label phase 2a study (NCT04405076) to evaluate the primary objectives of safety and immunogenicity of a single booster dose of mRNA-1273 or varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
335
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 382 publications
(385 citation statements)
references
References 16 publications
28
335
4
1
Order By: Relevance
“…In preliminary results at 6 months after two doses of mRNA-1273, neutralizing antibody levels against the Delta variant decreased compared to 28 days after the second dose of mRNA-1273 in the primary series, and approximately one-half of participants had no detectable neutralizing antibodies against the Delta variant in a pseudovirus research grade assay. 23 At 2 weeks after a booster dose of 50 µg of mRNA-1273, neutralizing antibody levels to the Delta variant increased to a similar level as neutralizing antibody titers against wild-type D614G at one month after the second dose of mRNA-1273 in the primary series. 23 The GMFR (Day 29 post-booster compared to pre-booster) achieved by mRNA-1273 booster, measured by the Delta variant pseudovirus assay (18.97; 95% CI, 16.72, 21.53), points to the ability of the mRNA-1273 vaccine booster to enhance a breadth of neutralizing antibody responses, including against the highly transmissible Delta variant.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In preliminary results at 6 months after two doses of mRNA-1273, neutralizing antibody levels against the Delta variant decreased compared to 28 days after the second dose of mRNA-1273 in the primary series, and approximately one-half of participants had no detectable neutralizing antibodies against the Delta variant in a pseudovirus research grade assay. 23 At 2 weeks after a booster dose of 50 µg of mRNA-1273, neutralizing antibody levels to the Delta variant increased to a similar level as neutralizing antibody titers against wild-type D614G at one month after the second dose of mRNA-1273 in the primary series. 23 The GMFR (Day 29 post-booster compared to pre-booster) achieved by mRNA-1273 booster, measured by the Delta variant pseudovirus assay (18.97; 95% CI, 16.72, 21.53), points to the ability of the mRNA-1273 vaccine booster to enhance a breadth of neutralizing antibody responses, including against the highly transmissible Delta variant.…”
Section: Discussionmentioning
confidence: 87%
“…23 At 2 weeks after a booster dose of 50 µg of mRNA-1273, neutralizing antibody levels to the Delta variant increased to a similar level as neutralizing antibody titers against wild-type D614G at one month after the second dose of mRNA-1273 in the primary series. 23 The GMFR (Day 29 post-booster compared to pre-booster) achieved by mRNA-1273 booster, measured by the Delta variant pseudovirus assay (18.97; 95% CI, 16.72, 21.53), points to the ability of the mRNA-1273 vaccine booster to enhance a breadth of neutralizing antibody responses, including against the highly transmissible Delta variant. Just as booster mRNA-1273 stimulated nAb levels against the original strain (GMTs 1892.7 at OL-D29 compared to 125.7 at OL-D1 (Supplementary Table 4), a booster injection of mRNA-1273 was able to broaden and increase nAb levels against the Delta variant, highlighting the critical benefits of mRNA-1273 booster dose.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…the third vaccine dose was found to be effective in further boosting antibody levels in elderly people [80], in solid organ transplant recipients [81], and in patients receiving maintenance hemodialysis or peritoneal dialysis [82]. The third dose was also effective in reinforcing immunity against VoC [83]. Irrespective of the demographical or clinical conditions that would blunt the anti-SARS-CoV-2 antibody response, the importance of monitoring humoral immunity seems almost unquestionable for prioritizing vaccine boosters, including new vaccines able to efficiently protect against current and potentially future SARS-CoV-2 drifted VoC.…”
Section: Discussionmentioning
confidence: 99%
“…Researches showed that novel coronavirus-19 vaccines (NCV) were of considerable e cacy, and improvement on e cacy, especially long-term protection, and exploration of new species of vaccines are being conducted [4][5][6][7][8]. Some new variants of COVID-19 have been emerging, which may exacerbate COVID-19 symptoms, while researches reveal that many still with good immunogenicity [9,10]. However, some studies show concern on prevention e cacy in the situation [11,12].…”
Section: Introductionmentioning
confidence: 99%